Cystatin-B Negatively Regulates the Malignant Characteristics of Oral Squamous Cell Carcinoma Possibly Via the Epithelium Proliferation/Differentiation Program - Xu, Tian-Tian; Zeng, Xiao-Wen; Wang, Xin-Hong; Yang, Lu-Xi; Luo, Gang; Yu, Ting (Frontiers in Oncology, 2021)
Disturbance in the proteolytic process is one of the malignant signs of tumours. Proteolysis is highly orchestrated by cysteine cathepsin and its inhibitors. Cystatin B (CSTB) is a general cysteine cathepsin inhibitor that prevents cysteine cathepsin from leaking from lysosomes and causing inappropriate proteolysis. Our study found that CSTB was downregulated in both oral squamous cell carcinoma (OSCC) tissues and cells compared to normal controls. Immunohistochemical analysis showed that CSTB was mainly distributed in the epithelial structure of OSCC tissues, and its expression intensity was related to the grade classification. A correlation analysis between CSTB and clinical prognosis was performed using gene expression data and clinical information acquired from The Cancer Genome Atlas (TCGA) database. Patients with lower expression levels of CSTB had shorter disease-free survival times and poorer clinicopathological features (e.g., lymph node metastases, perineural invasion, low degree of differentiation and advanced tumour stage). OSCC cell models overexpressing CSTB were constructed to assess the effects of CSTB on malignant biological behaviours, and upregulation of CSTB inhibited cell proliferation, migration and invasion in vitro. Weighted gene correlation network analysis (WGCNA) and gene set enrichment analysis (GSEA) were performed based on the TCGA data to explore potential mechanisms, and CSTB appeared to correlate with squamous epithelial proliferation-differentiation processes, such as epidermal cell differentiation and keratinization. Moreover, in WGCNA, the gene module most associated with CSTB expression (i.e., the brown module) was also the one most associated with grade classification. Upregulation of CSTB promoted the expression levels of markers (LOR, IVL, KRT5/14, and KRT1/10), reflecting a tendency for differentiation and keratinization in vitro. Gene expression profile data of the overexpressed CSTB cell line were obtained by RNA sequencing (RNA-seq) technology. By comparing the GSEA enrichment results of RNA-seq data (from the OSCC models overexpressing CSTB) and existing public database data, three gene sets (i.e., apical junction, G2/M checkpoint, etc.) and six pathways (e.g., NOTCH signalling pathway, glycosaminoglycan degradation, mismatch repair, etc.) were enriched in the data from both sources. Overall, our study shows that CSTB is downregulated in OSCC and might regulate the malignant characteristics of OSCC via the epithelial proliferation/differentiation program.